DEVELOPING CHILDREN'S RELIGIOUS AND MORAL VALUES IN RECOGNIZING GOOD AND BAD BEHAVIOR BY USING A COMBINATION OF PROBLEM BASED LEARNING (PBL) MODEL AND TALKING STICK MODEL WITH POP UP BOOK MEDIA IN GROUP B - Dita Sherina Maulida; Muhammad Dani Wahyudi (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2022)
AbstractThe purpose of this study is to determine teacher activities, children's activities and the results of developing children's religious and moral values in recognizing good and bad behavior. The method used qualitative type of Class Action Research (PTK), which is carried out 3 cycles with each cycle consisting of two meetings. The subjects of the study were 14 children. The instruments used are observation sheets related to teacher activities, children's activities, and developmental results. Data analysis using descriptive qualitative. The results showed that teacher activity increased with the category